Un nuovo Rover per il monitoraggio e campionamento delle acque - Greco, Manuel (GEOmedia, 2023)
We want to highlight the amphibious characteristics of the MAR vehicle (Multipurpose Amphibious Rover) through a deep analysis of its components and relating potentiality. MAR, thanks to its high versatility, can be used in several environments as platform both monitoring that carrying payloads such as sensors and electronic devices. It is particularly stable when moving on land, shallow water, snow and, therefore, in all those environments defined as “borderline” due to its low center of gravity. A key element of this vehicle is the polyethylene with which the external wheels are made allowing the rover to be very light. This feature would avoid damaging the marine flora and any submerged archaeological remains.